The correlation between Tamaddun Islamiyyah and pre-Islamic Arab culture. - Wildhan Ichza Maulana; Kamalludin Sasmito (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
This research focuses on the correlation between the socio-political conditions of pre-Islamic Arab society and the formation of Tamaddun Islamiyyah. The study aims to address the historical disintegration that exists within academic circles, where history is interpreted in various ways without a clear emphasis on the developing narrative. The goal of this study is to uncover the close correlation between pre-Islamic Arab historiography and the Tamaddun Islamiyyah project initiated by Prophet Muhammad. This research employs a descriptive-qualitative approach, utilizing socio-historical and Islamic history (Tārīkh Tasyrī') to analyze the nature, character, and influence of civilization. The study interprets and generalizes the historical facts surrounding this correlation. The data for this research is derived from various relevant historical literature sources. The findings of this study reveal that the correlation between Tamaddun Islam and pre-Islamic Arab civilization is aimed at eradicating Ashabiyyah, which is deeply rooted in Arab society.